2023
DOI: 10.3390/polym15132867
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan: Properties and Its Application in Agriculture in Context of Molecular Weight

Ramón Román-Doval,
Sandra P. Torres-Arellanes,
Aldo Y. Tenorio-Barajas
et al.

Abstract: Chitosan is a naturally occurring compound that can be obtained from deacetylated chitin, which is obtained from various sources such as fungi, crustaceans, and insects. Commercially, chitosan is produced from crustaceans. Based on the range of its molecular weight, chitosan can be classified into three different types, namely, high molecular weight chitosan (HMWC, >700 kDa), medium molecular weight chitosan (MMWC, 150–700 kDa), and low molecular weight chitosan (LMWC, less than 150 kDa). Chitosan shows sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 170 publications
0
8
0
Order By: Relevance
“…Recent research has indicated that PASP combined with urea could increase nitrogen accumulation in the upper part of sorghum, and improve nitrogen use efficiency and grain yield [8]; increase NR activity and promote nitrogen assimilation in maize seedlings [35]; and increase the activities of enzymes of nitrogen metabolism and the content of soluble protein in functional leaves of rice [21]. CTS, the other component of PAC, also has good adsorption and sustained-release effects, which can accelerate life activities of microorganisms in soil, promote soil respiration, improve nutrient availability [9], and the fertilizer absorption efficiency of plants [16]. Also, CTS can increase grain nitrogen accumulation and improve grain quality [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has indicated that PASP combined with urea could increase nitrogen accumulation in the upper part of sorghum, and improve nitrogen use efficiency and grain yield [8]; increase NR activity and promote nitrogen assimilation in maize seedlings [35]; and increase the activities of enzymes of nitrogen metabolism and the content of soluble protein in functional leaves of rice [21]. CTS, the other component of PAC, also has good adsorption and sustained-release effects, which can accelerate life activities of microorganisms in soil, promote soil respiration, improve nutrient availability [9], and the fertilizer absorption efficiency of plants [16]. Also, CTS can increase grain nitrogen accumulation and improve grain quality [36].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the advantages above, PASP has been widely applied in agriculture as the absorption promoter of fertilizers, a controlled-release agent, and so on [7,8]. CTS is a derivative of chitin and is considered the second most common polymer in the world after cellulose [9]. CTS has generated great attention in a range of fields due to its exceptional biological activities, such as biodegradability [10], biocompatibility [11], non-toxicity [12], and antimicrobial activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are a lot of studies related to the relationship between MM and DD of chitosan and its applications. Thus, the study by Román-Doval et al [ 11 ] showed the connection between different types of chitosan of different molar mass and its antifungal, antiviral, and antibacterial properties with applications in agriculture. The corresponding mechanism of different types of chitosan depends on both MM and DD.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding mechanism of different types of chitosan depends on both MM and DD. Low-molar-mass chitosan, via amino groups, can react much more easily with negatively charged bacterial cell membranes than high-molar-mass chitosan [ 11 ]. Joseph et al [ 6 ] reviewed, among other things, the properties and applications of chitosan depending on its molar mass and its degree of deacetylation.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [16] elucidated that the -NH 3 + group of deacetylated chitosan interacts electrostatically with the phosphoryl groups of microbial cell membranes, resulting in cell leakage. Chitosan also exhibits anti-fungal properties by directly impeding fungal growth and activating specific biological processes in plant tissue [17]. Its ability to inhibit gas exchange between fruits and their surroundings, thereby reducing respiration rates, positions chitosan as a compelling option for extending the post-harvest longevity of diverse produce, such as berry fruit [18], fresh fig [19], and mango [20].…”
Section: Introductionmentioning
confidence: 99%